2017
DOI: 10.18632/oncotarget.19862
|View full text |Cite
|
Sign up to set email alerts
|

Loss of p16INK4A stimulates aberrant mitochondrial biogenesis through a CDK4/Rb-independent pathway

Abstract: The tumor suppressor p16INK4A (p16) inhibits cell cycle progression through the CDK4/Rb pathway. We have previously shown that p16 regulates cellular oxidative stress, independent of its role in cell cycle control. We investigated whether loss of p16 had a direct impact on the mitochondria. We found that p16-null primary mouse fibroblasts (PMFs) displayed increased mitochondrial mass and expression of mitochondrial respiratory subunit proteins compared to wild-type (WT) PMFs. These findings in p16-null PMFs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…We observed that loss of p16 INK4A promotes melanocyte motility and the invasive and metastatic capacity of melanoma cells through the transcriptional activation of BRN2, a transcription factor previously associated with melanocytic invasive programs during both development and disease (Besch and Berking, 2014; Fane et al, 2017; Hoek and Goding, 2010; Pinner et al, 2009; Reed et al, 1995). These observations complement previous studies linking p16 INK4A to cellular motility via cytoskeletal and metabolic intermediates (Fahraeus and Lane, 1999; Tyagi et al, 2017). Thus the critical role of CDKN2A as a melanoma tumor suppressor gene involves not only the canonical mechanism of 16 INK4A preventing cell cycle entry and that of p14 ARF inducing the p53 pathway, but additionally includes the suppression of melanocyte migration.…”
Section: Discussionsupporting
confidence: 91%
“…We observed that loss of p16 INK4A promotes melanocyte motility and the invasive and metastatic capacity of melanoma cells through the transcriptional activation of BRN2, a transcription factor previously associated with melanocytic invasive programs during both development and disease (Besch and Berking, 2014; Fane et al, 2017; Hoek and Goding, 2010; Pinner et al, 2009; Reed et al, 1995). These observations complement previous studies linking p16 INK4A to cellular motility via cytoskeletal and metabolic intermediates (Fahraeus and Lane, 1999; Tyagi et al, 2017). Thus the critical role of CDKN2A as a melanoma tumor suppressor gene involves not only the canonical mechanism of 16 INK4A preventing cell cycle entry and that of p14 ARF inducing the p53 pathway, but additionally includes the suppression of melanocyte migration.…”
Section: Discussionsupporting
confidence: 91%
“…We found that mTORC1 upregulation downstream of p16 knockdown is independent of RB in multiple cell types. There are an increasing number of studies reporting RB-independent functions of p16 (Al-Khalaf et al, 2013; Jenkins et al, 2011; Lee et al, 2013; Tyagi et al, 2017), suggesting that the non-canonical pathway of p16 loss needs to be explored to identify both mechanistic underpinnings of RB-independent functions and novel therapies for cancer patients with p16-null tumors. As knockdown of p16 increased mTORC at the lysosomal membrane, it is possible that this pathway affects amino acid transporters and/or uptake.…”
Section: Discussionmentioning
confidence: 99%
“…p16 INK4a silencing was required for mitochondrial nucleoid remodeling in fs-HDF and WI-38 cells, and the regulation of p16 INK4 expression by siRNAs and decitabine in WI-38 and fs-HDF cells, respectively, changed induction of the nucleoid remodeling. Indeed, p16 INK4a regulates cell cycle via the CDK4/Rb-dependent pathway [45], and modulates mitochondrial dynamics and cell motility in mouse fibroblasts and human melanoma cells [46]. We report here the role of p16 INK4a as a regulator of mitochondrial nucleoid remodeling and mitochondrial biogenesis during induction of senescence via the p53-p21 WAF1 pathway.…”
Section: Discussionmentioning
confidence: 86%